College Libraries in Shimoga District: A Survey - Lohar, M. S.; Kumbar, Mallinath (Journal of Information and Knowledge, 2005)
The study evaluates the present situation of College Libraries in Shimoga District (Karnataka). A survey of 30-degree colleges is conducted through a questionnaire. The analysis of the collected data covers the organizational set-up of the library, library facilities, library resources, and services and physical facilities etc. Concludes that the present situation of the college libraries in Shimoga District do not meet the prescribed norms.